The provision of spiritual and pastoral care following stillbirth in Ireland: a mixed methods study. Issue 2 (10th June 2014) - Nuzum, Daniel; Meaney, Sarah; O'Donoghue, Keelin
Abstract : Background: The death of a baby is recognised as one of the most difficult bereavements with life-long impact for parents. How bereaved parents are cared for influences their grief journey. Optimal holistic care is provided when the physical, emotional, spiritual and social needs of parents are attended to. This study reviewed how spiritual care is provided to bereaved parents following stillbirth in maternity units in Ireland and the impact of stillbirth on healthcare chaplains. Methods: This was a mixed methods study using semistructured qualitative interviews with hospital chaplains in Irish maternity units. Quantitative data about the provision of services to bereaved parents were collated from the interviews. Qualitative data were analysed thematically to identify key themes. Results: 20 chaplains from 17 units participated in the study (85% of Irish maternity units). 12 chaplains (60%) are formally accredited chaplains; only one has received specialist training in perinatal bereavement care. 11 chaplains (55%) provide follow-up bereavement care. Seven chaplains (35%) did not feel part of the multidisciplinary team. The main themes that emerged were the impact of stillbirth, suffering and the challenge to faith creating inner conflict and doubt. Conclusions: The provision of spiritual care following stillbirth in Ireland is diverse. Spiritual care in this specialised area by chaplains who are not professionally trained and accredited potentially impacts quality and depth of care. Chaplains experience considerable impact and challenge to personal faith and belief as they provide care. Recommendations are made for ongoing education and greater support for chaplains.